Strategi Active Learning pada Pembelajaran Pendidikan Agama Islam Humanisme di Sekolah Dasar - syaifur - rohman; M. Choirul Muzaini (DIMAR: Jurnal Pendidikan Islam, 2022)
Humanism is a theory that emphasizes efforts to humanize humans and humanism theory tends to be abstract when compared to other learning theories, because in the study of humanism theory it is more towards discussing philosophy and psychology. Active learning (active learning) is an effort in order to develop the talents possessed by students, which are implemented in the types of discussion, practice and question and answer. In this study, the aim was to find out the implementation of the theory of active learning of humanism in Islamic Religious Education (PAI) learning and to find out the learning outcomes of Islamic Religious Education (PAI) using humanism theory with active learning strategies at SD Negeri Wijilan. This type of research is qualitative descriptive analysis, data collection techniques using observation, interviews and documentation. The results of this study are that the implementation of the theory of active learner humanism in learning Islamic Religious Education at SD Negeri Wijilan is well implemented and learning is going well, and has the goal of guiding students to do learning using active learning methods. This can be known by the occurrence of feedback (responses) and changes in student behavior towards positive actions, for example students becoming more active in the teaching and learning process, increasing student enthusiasm for learning, increasing students' memory and increasing moderate attitudes (tolerance).